Treating subclinical hypothyroidism in individuals with or without mental health problems –A Delphi based expert consensus study in two countries - Lieber, Ingrid; Van Der Feltz-Cornelis, Christina Maria; Razvi, Salman; Moriarty, Andrew S.; Wilkes, Scott; Ott, Michael; Mannchen, Julie; Eliasson, Mats; Werneke, Ursula (Frontiers in Endocrinology, 2023)
Subclinical hypothyroidism (SCH) is a common endocrine problem with prevalence estimates between 4% and 20%. Symptoms are often non-specific but can substantially affect well-being leading to repeated medical consultations. The effect of thyroid hormone replacement therapy (THRT) in patients with SCH remains uncertain. Current guidelines, limited by the lack of highquality evidence, have been controversial with limited adherence in clinical practice.Three-round modified Delphi method to establish consensus regarding diagnosis and treatment of individuals with SCH with and without affective disorder or anxiety, conducted with clinicians from three specialties, general practice, endocrinology and psychiatry, and two countries, Sweden and the United Kingdom.Sixty clinicians, 20 per specialty, were recruited. Fifty-three (88%) participants completed all three rounds. The participants reached consensus on five of the 26 practice statements that (a) repeated testing was required for the diagnosis of subclinical hypothyroidism, (b) antibody screening should usually occur, and (c and d) antibody screening would strengthen the indication for thyroid hormone replacement therapy in both individuals with or without affective disorder or anxiety. The participants disagreed with (e) a requirement of a TSH threshold ≥ 20 mIU/L for thyroid hormone replacement therapy start. Psychiatrists and GPs but not endocrinologists, agreed that there was a frequent discrepancy between laboratory results and clinical symptoms, and disagreed that testing for thyroid dysfunction was overused in patients presenting with depression or anxiety, or fatigue.In many aspects, attitudes toward diagnosing and treating SCH remain diverse. The inability of our Delphi panel to achieve consensus on most items and the disagreement with a TSH ≥ 20 mIU/L threshold for treatment suggest that the concept of SCH may need rethinking with a better understanding of the hypothalamic-pituitary-thyroid physiology. Given that the scientific evidence is currently not conclusive, guidelines in this area should not be taken as definitive.